Marginal Bone Resorption Around Dental Implants Placed in Alveolar Socket Preserved Sites: A 5 Years Follow-up Study - Beretta, Mario (J Maxillofac Oral Surg, 2020)
AIM: The present study evaluated the clinical and radiological stability of hard and soft tissues following alveolar socket preservation (ASP) procedure with a follow-up of 5 year from implant insertion. MATERIALS AND METHODS: The initial sample consisted of seven patients who underwent single tooth extraction and ASP procedure by means of demineralized bovine bone mineral particles covered with a porcine-derived non-cross-linked collagen matrix (CM). Each patient received a submerged single implant in the healed site. Mesial and distal peri-implant marginal bone resorption (MBR) rates were assessed radiographically at 1 year (T(1)) and 5 years (T(2)) after implant placement (baseline value). RESULTS AND STATISTICS: No dropouts occurred up to 5 years. At T(1), the MBR was 0.08 ± 0.16 mm at the mesial aspect and 0.1 ± 0.12 mm at the distal aspect. This difference was not statistically significant (P = 0.867). At T(2), the mesial MBR was 0.15 ± 0.17 mm and the distal MBR was 0.11 ± 0.14 mm, with a non-statistically significant difference (P = 0.532). Therefore, no statistically significant differences were detected comparing mesial and distal MBR at any time point. With respect to the intra-group comparisons, no differences were observed comparing the different study periods within each variable. Indeed, the comparison between T(0), T(1) and T(2) was non-statistically significant at both mesial (P = 0.06) and distal (P = 0.06) aspects. After 5 years, the volume of the soft tissues appeared clinically well maintained with a natural aspect around dental implants and adjacent teeth. CONCLUSION: ASP using demineralized bovine bone mineral in combination with CM proved to be an effective technique to maintain stable dimensional volumes of both hard and soft tissues.